خطبة طارق بن زياد قبل فتح الأندلس (دراسة تحليلية التأويلية) - Anas Rulloh, Mohammad (Journal of Arabic Language and Literature (ALLAIS), 2022)
This study discusses the meaning and interpretation in the text of Tariq bin Ziyad's sermon before the conquest of Andalusia with the interpretation or hermeneutic analysis method. The purpose of this study is to uncover the explicit and implicit meanings of Tariq bin Ziyad's sermon text before the conquest of Andalusia. This research uses the type of library research, because most of the data and sources of this research come from books and documents. The researcher uses the document study method in his research as a data collection method. As for verifying the validity of the data, the researchers used triangulation techniques. Using descriptive analysis in analyzing the data after analyzing the interpretation in the text of Tariq bin Ziyad's sermon before the conquest of Andalusia. We know that this sermon contains motivation, advice and wisdom.